Synthetic Conditions for High-Accuracy Size Control of PbS Quantum Dots - Zhang, Jianbing; Crisp, Ryan; Gao, Jianbo; Kroupa, Daniel M.; Beard, Matthew C.; Luther, Joseph M. (Journal of Physical Chemistry Letters, 2015)
Decreasing the variability in quantum dot (QD) syntheses is desirable for better uniformity of samples for use in QD-based studies and applications. Here we report a highly reproducible linear relationship between the concentration of ligand (in this case oleic acid, OA) and the lowest energy exciton peak position (nm) of the resulting PbS QDs for various hot-injection temperatures. Thus, for a given injection temperature, the size of the PbS QD product is purely controlled by the amount of OA. We used this relationship to study PbS QD solar cells that are fabricated from the same size of PbS QDs but synthesized using four different injection temperatures: 95, 120, 150, and 185 degrees C. We find that the power conversion efficiency does not depend on injection temperature but that the V-oc is higher for QDs synthesized at lower temperatures while the J(sc) is improved in higher temperature QDs.